2015
DOI: 10.1007/s12553-015-0099-x
|View full text |Cite
|
Sign up to set email alerts
|

How trustworthy are apps for maternal and child health?

Abstract: Mobile technologies have become important tools for promoting and implementing healthcare. A key feature of smartphones and tablet computers is their ability to run software applications (apps), which can address specific healthrelated areas, including maternal and child health; however, there is little independent regulation or guidance for the development and publication of health apps in many countries, including Australia. This research examined health apps in two major app stores (Google and Apple) that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 20 publications
0
43
0
2
Order By: Relevance
“…At the same time as the use of apps for medical and health-related purposes is becoming more common, several researchers are beginning to express concern about the validity and credibility of the information that the developers of health and medical apps provide 21,22 .…”
Section: Validity Privacy and Security Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time as the use of apps for medical and health-related purposes is becoming more common, several researchers are beginning to express concern about the validity and credibility of the information that the developers of health and medical apps provide 21,22 .…”
Section: Validity Privacy and Security Issuesmentioning
confidence: 99%
“…Their personal data are therefore very valuable to commercial entities 26 . One assessment of ten popular free apps relating to maternal and child health found significant variation in the quality of content, functionality and security 22 . Only three of the developers of the parenting and pregnancy apps that were studied had implemented a security mechanism to guarantee privacy and confidentiality.…”
Section: Validity Privacy and Security Issuesmentioning
confidence: 99%
“…Health, medical and fitness apps in general are notorious for leaking personal data and failing to encrypt data effectively [23,24]. One study found that only one in three pregnancy and parenting apps has implemented a security mechanism to guarantee privacy and confidentiality of the data that people were uploading [25].…”
Section: Introductionmentioning
confidence: 99%
“…We agree that vulnerable users, such as the elderly and those with mental health issues have specific needs and challenges in managing privacy and security concerns. We would argue that children are another vulnerable group (Benassi, 1999;Scott, Gome, Richards, & Caldwell, 2015). However, it was, and is, beyond the scope of our investigation to suggest how our general recommendations could be modified for, or implemented by, specific groups of users.…”
Section: Author Responsementioning
confidence: 94%